2019
DOI: 10.1021/acs.chemrev.8b00593
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning and Electrospun Nanofibers: Methods, Materials, and Applications

Abstract: Electrospinning is a versatile and viable technique for generating ultrathin fibers. Remarkable progress has been made with regard to the development of electrospinning methods and engineering of electrospun nanofibers to suit or enable various applications. We aim to provide a comprehensive overview of electrospinning, including the principle, methods, materials, and applications. We begin with a brief introduction to the early history of electrospinning, followed by discussion of its principle and typical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
2,383
0
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 3,299 publications
(2,731 citation statements)
references
References 1,013 publications
9
2,383
0
29
Order By: Relevance
“…As the same collector was used for all samples, this level of alignment in PANi4 was unexpected. However, it has been shown that conductive solutions for electrospinning result in thinner and more homogeneous fibers . The higher conductivity results in the development and extension of the charged jet along a straight line from the Taylor cone; this extension further faces a thinning and more uniform deposition on the ground collector.…”
Section: Resultsmentioning
confidence: 99%
“…As the same collector was used for all samples, this level of alignment in PANi4 was unexpected. However, it has been shown that conductive solutions for electrospinning result in thinner and more homogeneous fibers . The higher conductivity results in the development and extension of the charged jet along a straight line from the Taylor cone; this extension further faces a thinning and more uniform deposition on the ground collector.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning has been identified as a process of choice allowing the fabrication of such scaffolds with various polymers . During electrospinning, a polymer solution in a semi‐dilute entangled regime is pumped toward a metallic needle which is subjected to an electric field in the order of 1 kV cm −1 . The charged droplet exiting the needle takes the shape of the so‐called Taylor cone from which a jet is propelled toward a collector generally connected to the ground.…”
Section: From Nanoparticles and Polymers As Building Blocks To Smartmentioning
confidence: 99%
“…When decreasing the number of polymer chain entanglements in the solution, the resulting less viscous jet breaks into smaller droplets. Under these conditions, solid microparticles are deposited and the process is named electrospraying …”
Section: From Nanoparticles and Polymers As Building Blocks To Smartmentioning
confidence: 99%
“…[5][6][7] Specifically, uniaxially aligned nanofibers exhibit advantages in controlling the orientation, migration, and differentiation of cells, playing a critical role in guiding the regeneration of nerve, tendon, muscle, and vascular tissues. The nanofiber-based mats have shown great potential as scaffolds for applications in tissue engineering.…”
Section: Doi: 101002/marc201900579mentioning
confidence: 99%